2004
DOI: 10.1645/ge-3355
|View full text |Cite
|
Sign up to set email alerts
|

Differential Propagation of the Metazoan Parasite Myxobolus Cerebralis by Limnodrilus Hoffmeisteri, Ilyodrilus Templetoni, and Genetically Distinct Strains of Tubifex Tubifex

Abstract: Whirling disease, caused by the parasite Myxobolus cerebralis, has infected rainbow trout (Oncorhynchus mykiss) and other salmonid fish in the western United States, often with devastating results to native populations but without a discernible spatial pattern. The parasite develops in a complex 2-host system in which the aquatic oligochaete Tubifex tubifex is an obligate host. Because substantial differences in whirling disease severity in different areas of North America did not seem explainable by environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(112 citation statements)
references
References 38 publications
8
104
0
Order By: Relevance
“…In contrast, studies all across western North America have repeatedly demonstrated that T. tubifex oligochaetes belonging to Lineages IV, V and VI are refractory to M. cerebralis infection (DuBey & Caldwell 2004, DuBey et al 2005, Arsan et al 2007, Hallett et al 2009, Zielinski et al 2011, Nehring et al 2013. Likewise, Limnodrilus hoffmeisteri and Ilyodrilus templetoni are also refractory to the M. cerebralis parasite (Kerans et al 2004). These 2 species of tubificids are closely related to T. tubifex and often occur in sympatry with them in microhabitats laden with organically rich fine sediments in both lakes and streams.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, studies all across western North America have repeatedly demonstrated that T. tubifex oligochaetes belonging to Lineages IV, V and VI are refractory to M. cerebralis infection (DuBey & Caldwell 2004, DuBey et al 2005, Arsan et al 2007, Hallett et al 2009, Zielinski et al 2011, Nehring et al 2013. Likewise, Limnodrilus hoffmeisteri and Ilyodrilus templetoni are also refractory to the M. cerebralis parasite (Kerans et al 2004). These 2 species of tubificids are closely related to T. tubifex and often occur in sympatry with them in microhabitats laden with organically rich fine sediments in both lakes and streams.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested that tubificids that are not susceptible to infection by the M. cerebralis parasite might be capable of deactivating M. cerebralis myxospores in the aquatic environment (Kerans et al 2004, Beauchamp et al 2005, 2006, Nehring et al 2013. However, none of those studies were designed to directly address that possibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection in T. tubifex may persist for the duration of the worm's lifespan and release of TAMs can occur periodically over the span of at least a few years (Gilbert & Granath 2001). Infected worms suffer from suppressed feeding, reduced growth (Stevens et al 2001, Kerans et al 2004, Steinbach Elwell et al 2006, Rasmussen et al 2008) and inhibited reproductive development (Shirakashi & El-Matbouli 2009), though no obvious parasite effects on survival have been shown (Shirakashi & El-Matbouli 2009). Several studies have revealed the importance of environmental factors such as temperature and substrate (Kerans & Zale 2002) and water flow ) on the establishment and development of the parasite within T. tubifex.…”
Section: Introductionmentioning
confidence: 99%